2018
DOI: 10.1111/jcmm.13589
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal periodontal ligament as a novel adult stem cell source for regenerative corneal cell therapy

Abstract: Corneal opacities are a leading cause of global blindness. They are conventionally treated by the transplantation of donor corneal tissue, which is, restricted by a worldwide donor material shortage and allograft rejection. Autologous adult stem cells with a potential to differentiate into corneal stromal keratocytes (CSKs) could offer a suitable choice of cells for regenerative cell therapy. Postnatal periodontal ligament (PDL) contains a population of adult stem cells, which has a similar embryological origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 70 publications
(156 reference statements)
0
28
0
Order By: Relevance
“…41,42 In vitro differentiation of human embryonic stem cells into CSK-like cells via neural crest progenitors has also been reported, 43 but a number of issues, such as induction efficiency and control of cell purity and risk of tumorigenesis, need to be managed before any clinical application. Human bone marrow-and adipose-derived mesenchymal stem cells (MSCs), dental pulp stem cells, and periodontal ligament stem cells, when intrastromally injected into animal corneas, have been shown to assume CSK phenotypes, 33,[44][45][46][47][48] suggesting that these cell types could potentially be used in stromal cell therapy. However, natural differentiation of stem cells in a particular niche cannot achieve specific cell fate determination; hence not all differentiated cells can display a consistent profile of CSK features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41,42 In vitro differentiation of human embryonic stem cells into CSK-like cells via neural crest progenitors has also been reported, 43 but a number of issues, such as induction efficiency and control of cell purity and risk of tumorigenesis, need to be managed before any clinical application. Human bone marrow-and adipose-derived mesenchymal stem cells (MSCs), dental pulp stem cells, and periodontal ligament stem cells, when intrastromally injected into animal corneas, have been shown to assume CSK phenotypes, 33,[44][45][46][47][48] suggesting that these cell types could potentially be used in stromal cell therapy. However, natural differentiation of stem cells in a particular niche cannot achieve specific cell fate determination; hence not all differentiated cells can display a consistent profile of CSK features.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were treated with ice-cold 50 mM ammonium chloride (Sigma-Aldrich Corp.), saponin permeabilized, and blocked with 2% bovine serum albumin (BSA; Sigma-Aldrich Corp.) and 5% normal goat serum (NGS; Invitrogen, Carlsbad, CA, USA), followed by incubation with primary antibodies (Table 2) for 2 hours at room temperature. 33 For Kera and Lum immunostaining, sections were pretreated with endo-b-galactosidase (1.5 U/ mL in 10 mM phosphate buffer pH 7.4; Sigma-Aldrich Corp.) for 30 minutes at 378C prior to blocking and antibody incubation. After PBS washes, they were labelled with Red-X-or Alexa 488-conjugated IgG secondary antibody (Jackson ImmunoResearch Labs, West Grove, PA, USA) for 1 hour at room temperature, washed, and mounted with Fluoroshield with DAPI (4 0 ,6-diamidino-2-phenylindole; Santa Cruz Biotech, Santa Cruz, CA, USA) and viewed under fluorescence microscopy (Zeiss Axioplan 2; Carl Zeiss, Oberkochen, Germany).…”
Section: Ophthalmic Examination and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been done to isolate and characterize multipotent stem cells from various tissues in order to use their great potential in regenerative medicine. Bone marrow-derived mesenchymal stem cells (Islam et al, 2018), human umbilical cord mesenchymal stem cells (Yamashita et al, 2018), postnatal periodontal ligament (Yam et al, 2018), and limbal stem cells (Inatomi et al, 2018; Sasamoto et al, 2018) are recently studied stem cells sources in corneal wound healing and regeneration. Saghizadeh et al (2017) have recently reviewed all major stem cells usage in corneal wound healing.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…PDLSCs, on the other hand, express markers of MSC, embryonic and neural stem cells, and they exhibit multilineage potential in differentiating to adipocytes, chondrocytes, osteoblasts and neurons [78,80,81,82]. Our recent study has shown a robust two-step protocol involving spheroid formation and induction by growth factors and cytokines in a stromal niche, to differentiate human PDLSCs towards CSK-like cells with the expression of a broad spectrum of CSK markers [83]. Further work using animal models will delineate the functionality of these cells and assess their translational potential for stromal diseases.…”
Section: Mscs In Corneal Regenerationmentioning
confidence: 99%